Gender Stereotyping and Social Norms: Exploring Theoretical Perspectives and Educational Implications - Omojemite, Matthew Damilola; Cishe, Elphina Nomabandla; Zibongiwe, Mpongwana (Research in Social Sciences and Technology, 2024)
This review is a theoretical paper which examined gender stereotyping and social norms. The review was supported by feminist theory, critical theory and social psychology theory. The review utilizes a comprehensive strategy to investigate the theoretical lenses and consequences of gender stereotyping and social norms. The approach comprised of a few key stages. A survey incorporating gender stereotyping, social norms, feminist theory, critical theory and social psychology to assemble an all encompassing comprehension of the review was done. The review of gender stereotyping and social norms through critical assessment of key idea and viewpoints from feminist theory, critical theory and social psychology. The structure for revealing perplexing social peculiarities is given by the integration of feminist theory, critical theory and social psychology theory. This enlightened the basic component of inequality and injustice by considering the joint impact of gender, power and social setting. The review revealed the pervasive nature of gender stereotyping and social norms, their effect on causing inequality and injustice and the significance of promoting gender equality and social equity. In this way, the significance of interdisciplinary collaborative effort and combined actions in addressing the issue of gender stereotyping and social norms within educational setting and more extensive cultural setting. It emphasized the need for holistic approaches that will consider the broad intersection of power, ideology, and social issue in order to create gender equality and social justice both in the social and educational domain.